Acrylic Acid-Based Copolymers as Functional Binder for Silicon/Graphite Composite Electrode in Lithium-Ion Batteries. Issue 12 (1st January 2015) - Aoki, Shoko; Han, Zhen-Ji; Yamagiwa, Kiyofumi; Yabuuchi, Naoaki; Murase, Masahiro; Okamoto, Kuniaki; Kiyosu, Takahiro; Satoh, Michihiko; Komaba, Shinichi
Abstract : Acrylic acid-based copolymers are synthesized by polymerization of acrylic acid with a small portion of crosslinker, diallyl ethers. The obtained copolymers are soluble in water, and viscosity of their aqueous solution incrementally varies with increase in the amount of crosslinker and neutralization degree of -COOH groups with NaOH. The copolymers are examined as binders for silicon/graphite composite electrodes for lithium-ion batteries. Reversibility and lithiation capacity of the composite are highly improved by the selection of copolymers, which is due to better homogeneity and mechanical durability of the composite electrodes.